Evaluation of Provider Screening Practices for Fracture Risk Assessment among Patients with HIV Disease - Faryal Mirza; Sabina Zawadzka; Anne Abbate; Michael Thompson; Dorothy Wakefield; Lisa M. Chirch (AIDS Research and Treatment)
People living with HIV are known to have greater risk of low bone mineral density than HIV-negative peers. The reasons for this disparity are multifactorial. To address this increased risk, the Infectious Diseases Society of America (IDSA) released fracture risk screening recommendations in 2015, which differ significantly from recommendations that apply to the general population. A study was conducted at the University of Connecticut to assess for provider awareness and adherence to these recommendations. Electronic surveys were sent to providers, and patients were also surveyed for risk factors and prevalence of low bone mineral density. The results of the provider survey showed low rates of awareness of the IDSA screening recommendations. A substantial proportion of patients surveyed met criteria for low BMD screening but did not have dual-energy X-ray absorptiometry (DXA) ordered by their provider. As an intervention, providers were sent information via e-mail regarding current screening recommendations, as well as notifications if their patient met criteria for DXA screening. A twelve-month follow-up survey showed increased provider knowledge of screening recommendations and improved screening practices. Additionally, the results of a logistic regression analysis of patient factors showed that increasing age and male sex were positively associated with fragility fracture risk. Increased duration of antiretroviral therapy use was associated with a lower likelihood of fragility fracture.